2022
DOI: 10.1158/1535-7163.mct-22-0312
|View full text |Cite
|
Sign up to set email alerts
|

Endo180 (MRC2) Antibody–Drug Conjugate for the Treatment of Sarcoma

Abstract: Although the 5-year survival rates for sarcoma patients have improved, the proportion of patients relapsing after first line treatment remains high and survival of patients with metastatic disease is dismal. Moreover, the extensive molecular heterogeneity of the multiple different sarcoma subtypes poses a substantial challenge to developing more personalized treatment strategies. From immunohistochemical staining of a large set of 625 human soft tissue sarcomas we demonstrate strong tumor cell staining of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…uPARAP (product of MRC2 gene, also known as Endo180 or CD280) is a highly interesting target. It is an endocytic receptor that collagen binds to, and uP-ARAP plays an important role in tissue collagen turnover [110,119,120]. On healthy cells, uPARAP expression is limited, but there is a high level of expression on tumor cells including glioblastoma, mesothelioma, osteosarcoma, STS, bone sarcoma, and acute myeloid leukemia [110,119,120].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…uPARAP (product of MRC2 gene, also known as Endo180 or CD280) is a highly interesting target. It is an endocytic receptor that collagen binds to, and uP-ARAP plays an important role in tissue collagen turnover [110,119,120]. On healthy cells, uPARAP expression is limited, but there is a high level of expression on tumor cells including glioblastoma, mesothelioma, osteosarcoma, STS, bone sarcoma, and acute myeloid leukemia [110,119,120].…”
Section: Discussionmentioning
confidence: 99%
“…It is an endocytic receptor that collagen binds to, and uP-ARAP plays an important role in tissue collagen turnover [110,119,120]. On healthy cells, uPARAP expression is limited, but there is a high level of expression on tumor cells including glioblastoma, mesothelioma, osteosarcoma, STS, bone sarcoma, and acute myeloid leukemia [110,119,120]. In vitro studies with the tubulin inhibitor MMAE-ADC directed against uPARAP showed strong cytotoxicity in uPARAP-positive sarcoma cancer cell lines [110,119].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Evans et al reported that the Endo180 receptor is highly expressed in human soft-tissue sarcomas; at the same time, Endo180 is also a circular transmembrane receptor, which makes it an ideal target for treating ADCs. 27 By using antibodies targeting nontumor tissues, ADCs have also been designed to treat other diseases. Yu et al reviewed antibody-antimicrobial conjugates made from antibodies targeting bacteria-related targets that can be used as antibacterial drugs.…”
Section: Components and Technological Advances Of Adcsmentioning
confidence: 99%